Significant increase of flow kinetic energy in "nonresponders" patients to cardiac resynchronization therapy. Issue 5 (23rd March 2017) - Cimino, Sara; Palombizio, Dino; Cicogna, Francesco; Cantisani, Donatella; Reali, Manuela; Filomena, Domenico; Petronilli, Valentina; Iacoboni, Carlo; Agati, Luciano
Abstract : Backgrounds: It's still unclear if different patterns of intraventricular flow dynamics may be detected in patients nonresponders to cardiac resynchronization therapy (CRT) as compared to responders ones. Aim of this study was to evaluate the characteristics of left ventricular (LV) flow dynamics 6‐months after CRT to identify Echo‐particle imaging velocity (PIV) patterns were more frequently detected in nonresponders patients. Methods: Thirty‐two patients with dilated cardiomyopathy, undergoing CRT, were enrolled in this study. All patients underwent 2D and 3D echo and fluid dynamics assessment 6 months after CRT, during active CRT (CRT‐ON) and during a temporarily discontinued state (CRT‐OFF). LV volumes systolic and diastolic volumes (LVESV and LVEDV), ejection fraction (LVEF), global longitudinal strain (GLS), systolic dyssynchrony index (SDI), and several geometrical and functional Echo‐PIV‐derived parameters were calculated. Patients were divided in two groups: "responders" to CRT (decrease in LVESV>15% 6 months after CRT) and "nonresponders." Results: During CRT‐OFF, LVEF, GLS were lower, while SDI and LVESV were higher in nonresponders group ( P =.030, P =.051, P =.035, and P =.025, respectively). Energy dissipation, vortex area, and vorticity fluctuation were higher in "nonresponders" patients during CRT‐OFF ( P =.038, P =.054, and P =.035, respectively). During CRT‐ON, energy dissipation, vortex area, and vorticity fluctuation further increase in nonresponders patients ( P =.020, P =.038, and P =.030, respectively) with a concomitant worsening of SDI ( P =.045). Conclusion: Our data show a significant worsening in flow‐derived parameters in CRT "nonresponders" patients as compared with responders. Further larger longitudinal studies are necessary to assess whether these more chaotic intraventricular flow‐patterns may contribute to a persistent adverse remodeling observed in this subset of patients.